Sosialisasi dan Simulasi Akuntansi Mudharabah pada PT. Amanah Baitullah Tur Pekanbaru - Helly Aroza Siregar; Dominicus Josephus Swanto; Hidayat Syahputra; Ria Darmasari; Ienne Yoseria Putri (JUDIKAT: Jurnal Pengabdian Kepada Masyarakat, 2021)
The use of mudharabah accounting has been regulated in PSAK 105 concerning Mudharabah Accounting. But until now, only financial institutions that use this sharia accounting system. Meanwhile, financial management and company administration can also apply mudharabah accounting so that the company's financial management can be carried out in accordance with Islamic law in an effort to seek blessings. Based on this background, mudharabah accounting socialization was carried out at PT. Amanah Baitullah Tour Pekanbaru which aims to introduce mudharabah accounting to the fund owner (shahibul maal) and the fund manager (mudharib). While the simulation of the use of mudharabah accounting is carried out to provide knowledge to fund managers and administrative and financial staff to be able to know and be able to calculate business profit sharing and be able to make financial reports based on mudharabah principles. The method used is in the form of lectures and simulations. The socialization activity was successfully carried out in front of seven fund owners, one director and two administrative and financial staff. The socialization provided is related to theories regarding mudharabah accounting based on expert opinion and in accordance with PSAK 105 concerning Mudharabah Accounting. While the simulation is given in the form of profit sharing calculations and transaction journal based on mudharabah accounting.